Evidance Based Practice Penerapan Expressive Writing Therapy dalam Mengontrol Halusinasi pada Gangguan Persepsi Sensori: Halusinasi Pendengaran - Kaligis, Yosua Aldrin; Keles, Firginia F. F. (Yayasan Syalom Cipta Sumikolah, 2025)
Hallucinations are sensory perception disorders in which the patient expresses or feels something that is not real. The most common hallucination experienced by patients is auditory hallucinations. This case study aims to carry out comprehensive nursing care with the application of expressive writing therapy at Dr. V. L Ratumbuysang Mental Hospital. As a result of the study with the application of expressive writing therapy carried out for 3 days, the results of the evaluation found that expressive writing therapy was effective in controlling hallucinations in Mr. J from the beginning of often hearing whispering sounds until they became rarely heard and the client felt more relieved. Conclusion: this scientific paper is effective in controlling hallucinations in Mr. J with sensory perception disorders: auditory hallucinations. Advice: to all health workers to be able to provide expressive writing therapy actions and education to clients who have sensory perception disorders: auditory hallucinations.